DEVELOPMENT OF YIELD LOSS ASSESSMENT MODEL FOR POTATO LATE BLIGHT DISEASE IN INDO-GANGETIC PLAINS - Lal, Mehi; Sharma, Sanjeev; Ahmad, Islam; Singh, B P; Yadav, Saurabh (Potato Journal, 2015)
Late blight is the most dreaded disease of potato throughout the world. Experiments were conducted during the years 2004-05 to 2012-13 at Central Potato Research Institute Campus, Modipuram, Meerut, Uttar Pradesh to assess late blight severity and determine yield losses for the development of yield loss assessment model. The dynamics of late blight were monitored with application of different fungicides. The model has two parameters i.e. per cent yield loss as a dependent variable and AUDPC an independent variable. Twenty five linear and non linear regression lines were fitted with three years data and best non linear reciprocal hyperbola regression line (R2 =0.84) was selected. The model revealed deviation from 0.5 to 13.70% in 2010-11, 1.16 to 9.69% in 2011-12 and -3.01 to 9.23% in 2012-13 between actual and predicted yield loss. Highest deviation (13.70%) was found in the treatment mancozeb in alternation with metalaxyl + mancozeb (2 sprays) and least in the treatment cymoxanil + mancozeb (3 sprays) treatment during 2010-11. Significant correlation was found between yield and AUDPC values.